Accelerated Zincations for an Efficient and Mild Functionalization of Aromatics and Heterocycles. Issue 5 (15th March 2013) - Unsinn, Andreas; Wunderlich, Stefan H.; Knochel, Paul
Abstract An improved process for the preparation of aromatic and heteroaromatic diorganozinc reagents and their subsequent reaction with electrophiles is presented. The new method, featuring the use of a 2, 2, 6, 6‐tetramethylpiperidyl (TMP) magnesium base in the presence of zinc chloride (ZnCl2), is superior to the previous methods, which require the preparation of zinc bases. Specifically, the shorter reaction times under mild conditions provide an easier and more practical process, while the use of only a slight excess of the amide allows the isolation of products in high yields. These improvements are particularly significant for the large‐scale preparation of organozincs and their subsequent reactions. Remarkably, beside the high kinetic activity, a wide range of functional groups is tolerated and sensitive heteroaromatics can easily be converted into the corresponding organometallic reagents and reacted with various electrophiles.